Social Comparison of Expertise: Interactional Patterns and Dynamics of Instruction - Liengme Bessire, Marie-Jeanne; Grossen Peretti, Michèle; Iannaccone, Antonio; Perret-Clermont, Anne-Nelly (My University, 1994)
The aim of the present study is to examine the effects of social comparison on individual performance after an interaction session and the variation of the interactional dynamics depending upon the reciprocal perception children have of their level of expertise. The experiment is a protest-Interaction-posttest design with two experimental conditions manipulating the reciprocal perception ail expert and a novice have of their level of expertise. Results show thal the novices gain more Individual benefits when they think they have the same level of expertise as the expert during the interaction session than when they believe themselves to have a lower level of expertise. Further results concerning the lnteractional dynamics of the interaction session show that there are more collaborative patterns when the children perceive themselves as equal. The presentation of the latter results will constitute the core of this paper.